2018
DOI: 10.5230/jgc.2018.18.e10
|View full text |Cite
|
Sign up to set email alerts
|

Successful Robotic Gastrectomy Does Not Require Extensive Laparoscopic Experience

Abstract: PurposeWe evaluated the learning curve and short-term surgical outcomes of robot-assisted distal gastrectomy (RADG) performed by a single surgeon experienced in open, but not laparoscopic, gastrectomy. We aimed to verify the feasibility of performing RADG without extensive laparoscopic experience.Materials and MethodsBetween July 2012 and December 2016, 60 RADG procedures were performed by a single surgeon using the da Vinci® Surgical System (Intuitive Surgical). Patient characteristics, the length of the lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Also, the learning curve may be better for adoption by surgeons who may not be facile in laparoscopic surgery. [7][8][9] However, the data comparing robotic surgery to laparoscopic surgery are limited to small numbers and mostly retrospective in nature. 6,10,11 Furthermore, most of the studies comparing the 2 approaches are from East Asia or from high-volume centers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the learning curve may be better for adoption by surgeons who may not be facile in laparoscopic surgery. [7][8][9] However, the data comparing robotic surgery to laparoscopic surgery are limited to small numbers and mostly retrospective in nature. 6,10,11 Furthermore, most of the studies comparing the 2 approaches are from East Asia or from high-volume centers.…”
Section: Introductionmentioning
confidence: 99%
“…In literature [ 18 , 55 , 56 ], it was demonstrated that robotic surgery requires a shorter learning curve as compared to conventional laparoscopy and that surgeons without extensive experience in laparoscopic gastrectomy can safety perform RADG with acceptable surgical outcomes. An [ 57 ] affirmed that surgeons with experience in open gastrectomy can easily achieve the stabilization of the duration of RADG after 25 cases. According to these findings, performing robotic total gastrectomy with handsewn intracorporeal anastomosis after an adequate learning curve with RADG represents a good option for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery can be performed safely with acceptable surgical outcomes by experts in open gastrectomy, with the learning curve for robotic gastrectomy being significantly overcome by a sufficient experience with laparoscopic gastrectomy [272829]. The shorter hospitalization time observed in patients who underwent TRDG may be due to the performance of a surgeon with extensive laparoscopic experience, including stable and proficient dissection techniques.…”
Section: Discussionmentioning
confidence: 99%